The extent and determinants of diabetes and cardiovascular disease comorbidity in South Africa - results from the South African National Health and Nutrition Examination Survey (SANHANES-1) - Chipo Mutyambizi; Lumbwe Chola; Wim Groot; Milena Pavlova; Demetre Labadarios; Charles Hongoro (BMC, 2017)
Abstract Background Diabetes is a major health problem and cause of death worldwide. It is predicted that the prevalence of diabetes will increase from 415 million in 2015 to 642 million in 2040. However, the burden of diabetes in low- and middle-income countries is not clearly understood, particularly its interaction with other chronic illnesses. This study investigates the self-reported prevalence of and factors associated with diabetes and cardiovascular comorbidity in South Africa. Methods Data used in this study are from the 2012 South African National Health and Nutrition Examination Survey; a nationally representative cross-sectional household survey (N = 25,532). Diabetes and cardiovascular disease comorbidity was defined as the coexistence of diabetes plus one or more cardiovascular diseases reported at the time of the survey. This study makes use of multinomial logistic regression models to analyse the relationship between diabetes - cardiovascular disease comorbidity and several predictors including race, income, socio-economic status and obesity. Results According to the survey data we analysed, 5% of South Africans aged 15 and above had self-reported diabetes in 2011-2012. Among those with self-reported diabetes, 73% had at least one additional cardiovascular chronic illness. Diabetes and its cardiovascular disease comorbidity was more prevalent in Africans (66%), females (66%), those who lived in urban areas (75%), had secondary education (44%) and were unemployed (62%). Factors strongly associated with diabetes - cardiovascular disease comorbidity were older age (Odds ratio [OR] 1.09; 95% Confidence Interval [CI] 1.06-1.12), high household income (0.27; 0.10-0.76) versus low income, moderate (0.33; 0.11-0.96) and good self-rated health (0.24; 0.08-0.68) versus bad self-rated health, occasional (0.29; 0.10-0.88) and regular smokers (0.25; 0.12-0.53) versus non-smokers and physical activity (0.15; 0.03-0.68) versus no physical activity. Conclusion The study provides insight into the factors associated with cardiovascular disease comorbidity in diabetic individuals. The findings indicate that there are differences in the factors associated with diabetes and those associated with diabetes - cardiovascular disease comorbidity. This provides information, which can be used to design programmes that encourage healthy lifestyles in people living with diabetes.